Intravitreal panitumumab and myopic macular degeneration - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Holz, Frank G.; Panda-Jonas, Songhomitra; Gilemzianova, Leisan I.; Khakimov, Dinar A.; Jonas, Jost B. (British journal of ophthalmology, 2023)
Background: In experimental studies, intravitreally applied antibodies against epidermal growth factor (EGF), EGF family members (amphiregulin, neuregulin-1, betacellulin, epigen, epiregulin) and against the EGF receptor (EGFR) were associated with a reduction in lens-induced axial elongation and decrease in physiological eye elongation in guinea pigs and in non-human primates. Here, we investigated the intraocular tolerability and safety of a fully human monoclonal IgG2-antibody against EGFR, already in clinical use in oncology, as a potential future therapeutic approach for axial elongation in adult eyes with pathological myopia. - Methods The clinical, monocentre, open-label, multiple-dose, phase-1 study included patients with myopic macular degeneration of stage 4, who received intravitreal injections of panitumumab in various doses and in intervals ranging between 2.1 months and 6.3 months. - Results The study included 11 patients (age:66.8±6.3 years), receiving panitumumab injections in doses of 0.6 mg (4 eyes; 1×1 injection, 3×2 injections), 1.2 mg (4 eyes; 1×1 injection, 2×2 injections, 1×3 injections) and 1.8 mg (3 eyes; 1×1 injection, 2×2 injections), respectively. None of the participants showed treatment-emergent systemic adverse events or intraocular inflammatory reactions. Best-corrected visual acuity (1.62±0.47 logarithm of the minimal angle of resolution (logMAR) vs 1.28±0.59 logMAR; p=0.08) and intraocular pressure (13.8±2.4 mm Hg vs 14.3±2.6 mm Hg; p=0.20) remained unchanged. In nine patients with a follow-up of >3 months (mean:6.7±2.7 months), axial length did not change significantly (30.73±1.03 mm vs 30.77±1.19 mm; p=0.56). - Conclusions In this open-labelled, phase-1 study with a mean follow-up of 6.7 months, panitumumab repeatedly administered intravitreally up to a dose of 1.8 mg was not associated with intraocular or systemic adverse effects. During the study period, axial length remained unchanged. - Trial registration number DRKS00027302.
Gesehen am 20.02.2024